1971
DOI: 10.1149/1.2407900
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Cholesteric Films to Ultraviolet Exposure

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In 1974, Haas et al prepared CLC mixtures based on chlorostilbenes and cholesteryl oleyl carbonate and demonstrated a light-induced CLC to isotropic (CLC / I) transition. 82,83 These mixtures of nematic chlorostilbenes with cholesteryl oleyl carbonate were focal conic at room temperature, whereas after exposure to UV light the exposed regions became isotropic and transparent. Mioskowski et al developed a photoresponsive CLC mixture based on the photodecarbonylation of chiral ketones.…”
Section: A Photoresponsive Non-liquid Crystalline Materialsmentioning
confidence: 99%
“…In 1974, Haas et al prepared CLC mixtures based on chlorostilbenes and cholesteryl oleyl carbonate and demonstrated a light-induced CLC to isotropic (CLC / I) transition. 82,83 These mixtures of nematic chlorostilbenes with cholesteryl oleyl carbonate were focal conic at room temperature, whereas after exposure to UV light the exposed regions became isotropic and transparent. Mioskowski et al developed a photoresponsive CLC mixture based on the photodecarbonylation of chiral ketones.…”
Section: A Photoresponsive Non-liquid Crystalline Materialsmentioning
confidence: 99%
“…Adams and Haas investigated the pitch change in cholesteryl nonanoate/cholesteryl iodide by ultraviolet (UV) irradiation. [37,38] Upon irradiation, photodecomposition of cholesteryl iodide reduces its ratio in the mixed system, thus resulting in a cholesteric pitch change. In studies concerning the effect of a small amount of a photochromic dopant, Sackmann reported a pitch change induced by reversible photochemical reactions such as photoisomerization of azobenzene and stilbene in a mixture of cholesteryl chloride and cholesteryl nonanoate.…”
Section: Photochemical Control Of Cholesteric Pitchmentioning
confidence: 99%